Outage and Capacity Performance Evaluation of Distributed MIMO Systems over a Composite Fading Channel. (29th September 2014) - Peng, Wenjie; Li, Yueheng; Ju, Meiyan; Huang, Ping; Tan, Guoping; Jiang, Defu
Abstract : The exact closed-form expressions regarding the outage probability and capacity of distributed MIMO (DMIMO) systems over a composite fading channel are derived. This is achieved firstly by using a lognormal approximation to a gamma-lognormal distribution when a mobile station (MS) in the cell is in a fixed position, and the so-called maximum ratio transmission/selected combining (MRT-SC) and selected transmission/maximum ratio combining (ST-MRC) schemes are adopted in uplink and downlink, respectively. Then, based on a newly proposed nonuniform MS cell distribution model, which is more consistent with the MS cell hotspot distribution in an actual communication environment, the average outage probability and capacity formulas are further derived. Finally, the accuracy of the approximation method and the rationality of the corresponding theoretical analysis regarding the system performance are proven and illustrated by computer simulations.